2018
DOI: 10.1136/ebmental-2018-300050
|View full text |Cite
|
Sign up to set email alerts
|

Twenty years of research on attention-deficit/hyperactivity disorder (ADHD): looking back, looking forward

Abstract: In this clinical review we summarise what in our view have been some the most important advances in the past two decades, in terms of diagnostic definition, epidemiology, genetics and environmental causes, neuroimaging/cognition and treatment of attention-deficit/hyperactivity disorder (ADHD), including: (1) the most recent changes to the diagnostic criteria in the Diagnostic and Statistical Manual of Mental Disorders and International Classification of Diseases; (2) meta-analytic evidence showing that, after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
82
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 41 publications
(29 reference statements)
1
82
3
5
Order By: Relevance
“…The causes of ADHD have not yet been completely understood [3]. Twin and adoption studies have shown that heritability of ADHD is between 60% and 90% [4].…”
Section: Introductionmentioning
confidence: 99%
“…The causes of ADHD have not yet been completely understood [3]. Twin and adoption studies have shown that heritability of ADHD is between 60% and 90% [4].…”
Section: Introductionmentioning
confidence: 99%
“…The article by Cortese and Coghill comprehensively highlights the recent advances in attention-deficit/hyperactivity disorder (ADHD) research in terms of causes, diagnosis and treatment 1. The effort to understand the current status of the research is laid systematically and the lacunas in Diagnostic and Statistical Manual Of Mental Disorders  (DSM) criteria, prevalence estimation, exact role of environmental and genetic contribution have been addressed well.…”
mentioning
confidence: 99%
“…This can often lead to overdiagnosis (causing side effects related to medicine) or underdiagnosis (worsening of symptoms). As ADHD can emerge as de novo in adulthood,1the need of the hour is diagnosis on the basis of objectivity and identification of the reliable functional markers of cognitive deficits.…”
mentioning
confidence: 99%
“…We thank Leon and colleagues1 for highlighting a topic, namely the role of QEEG (quantitative electroencephalogram) in the management of attention-deficit/hyperactivity disorder (ADHD) that, due to space constraints, we could not address in our review 2…”
mentioning
confidence: 99%